Fenomena TikTok Shop dan TikTok Live sebagai Dampak Economic Decline Post-Covid - Adzra Fathonah; Kayla Khairunisa; Sri Handayani (Universitas Serambi Mekkah, 2025)
The development of the digital economy has driven a major transformation in how Micro, Small, and Medium Enterprises (MSMEs) market and sell their products, particularly through social media platforms such as TikTok. This study aims to examine the role of TikTok Shop in enhancing the competitiveness of local MSMEs amidst shifting consumer behavior in the post-pandemic era. Using a literature review method from various relevant journals and articles, the study finds that TikTok Shop offers significant opportunities for MSMEs to reach broader markets through short video content, live streaming features, and seamless transaction systems. TikTok Live has proven effective in fostering emotional engagement and consumer trust through real-time interaction and product visualization. However, challenges such as competition with large brands and the need to follow fast-changing trends also emerge as consequences of rapid digitalization. The findings suggest that TikTok Shop contributes positively to MSMEs' digital adaptation and promotes local economic growth in the digital era.